Cryopreservation of Multicellular Spheroids Derived From Rabbit Dermal Papilla Cells - Novikova, Oksana Yu.; Bondarenko, Tatyana P.; Bozhok, Galina A. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 177.